Opportunistic screening for osteoporosis correlating the bone densities of jaws with multislice computed tomography for cervical vertebrae - Cheade, Mayara de Cassia Cunha; Munhoz, Luciana; Arita, Emiko Saito; Watanabe, Plauto Christopher Aranha (Clinical and Laboratorial Research in Dentistry, 2019)
Objectives: to evaluate the correlation of the bone mineral density (BMD) from maxilla and mandible with that of the cervical vertebrae, using Hounsfield units (HU) and multislice computed tomography (CT) to verify whether CT could be a useful osteoporosis screening tool. Methods: 79 multislice CT examinations from patients who underwent CT examinations of maxilla, mandible and cervical vertebrae simultaneously were included. The following left and right anatomical regions were assessed: mandible ramus; mandible head; the area below the inferior first molar and the area below the upper cuspids. HU were measured in each area using a 0.1 cm region of interest (ROI) positioned in the center of the slice. Results: a significant correlation between the cervical spine and the posterior region of the mandible was found, as well as a significant correlation between the anterior maxilla and the cervical spine. However, no correlation was found between the cervical spine and other parts of the mandible, such as ramus and head of mandible. Conclusions: As anterior maxillary bone and posterior mandible bone HU values correlate with cervical bone HU values, this examination may be applied as osteoporosis screening tool.